Hydrotropic polymer-based paclitaxel-loaded self-assembled nanoparticles: preparation and biological evaluation. Issue 53 (30th June 2017) - Gao, Lipeng; Gao, Liefang; Fan, Mingxue; Li, Qilong; Jin, Jiyu; Wang, Jing; Lu, Weiyue; Yu, Lei; Yan, Zhiqiang; Wang, Yiting
Abstract : Hydrotropic polymer-based paclitaxel-loaded self-assembled nanoparticles: preparation and biological evaluation. Abstract : The poor compatibility of carrier materials with drugs is one of the main obstacles in the drug encapsulation of nano-drug delivery system (NDDS), hindering the clinical translation of NDDS. In this study, using paclitaxel (PTX) as the insoluble model drug, we conjugated N, N -diethylniacinamide (DENA), a hydrotropic agent of PTX, to the backbone of poly(l -γ-glutamyl-glutamine) (PGG), a water-soluble polymer, to prepare the "hydrotropic polymer" PGG–DENA to improve its compatibility with PTX. By virtue of the hydrotropic effect of the DENA group, PTX was encapsulated by PGG–DENA to obtain the hydrotropic polymeric nanoparticles (PGG–DENA/PTX NPs). PTX-conjugated poly(l -γ-glutamyl-glutamine) acid (PGG–PTX) NPs previously reported were used as the control in the study. The PGG–DENA/PTX NPs showed a z -average hydrodynamic diameter of about 70 nm, and good long-term stability in PBS solution at 4 °C. The cumulative release rate of PTX from PGG–DENA/PTX NPs reached 79.10% at 96 h, while that of PGG–PTX NPs was 22.96%. PGG–DENA/PTX NPs showed significantly increased in vitro cytotoxicity on NCI-H460 lung cancer cells compared with PGG–PTX NPs. The hemolysis study proved that the PGG–DENA/PTX NPs has good biocompatibility. These results indicated that by introducing the hydrotropic agent DENA, the hydrotropic polymer PGG–DENA becomes an effective carrier material of PTX. This study provides a solution to increase the compatibility of carrier materials with insoluble drugs, and also may provide an effective way to develop a series of personalized carrier materials suitable for different insoluble drugs.